Tremendous enhancements of isoflavonoid biosynthesis, associated gene expression and antioxidant capacity in Astragalus membranaceus hairy root cultures elicited by methyl jasmonate. Issue 5 (May 2016) - Gai, Qing-Yan; Jiao, Jiao; Luo, Meng; Wang, Wei; Gu, Cheng-Bo; Fu, Yu-Jie; Ma, Wei
Graphical abstract: Highlights: MJ, SA and ASA were applied for enhancing isoflavonoid biosynthesis in AMHRCs. AMHRCs augmented isoflavonoid production 9.71-fold when elicited with MJ. Transcriptions of eight isoflavonoid biosynthetic genes were monitored by qRT-PCR. Limiting steps of isoflavonoid biosynthesis were probably controlled by CHI and IFS genes. Abstract: In this work, Astragalus membranaceus hairy root cultures (AMHRCs) were induced to boost isoflavonoid biosynthesis upon elicitations of methyl jasmonate (MJ), salicylic acid (SA) and acetylsalicylic acid (ASA). The optimal enhancement of isoflavonoid production was obtained in 34 day-old AMHRCs elicited by MJ under the concentration of 283 μM and the exposure time of 33.75 h. The resulting isoflavonoid yield was 2250.10 ± 71.88 μg/g dry weight (DW), which tremendously increased 9.71-fold relative to that of non-treated control (231.64 ± 6.51 μg/g DW). Moreover, transcriptions of eight isoflavonoid biosynthetic genes were significantly up-regulated in response to MJ elicitation, and chalcone isomerase and isoflavone synthase genes were found to be key regulatory nodes in isoflavonoid biosynthetic pathway. Additionally, an enormous increase was observed in antioxidant capacities of extracts from MJ-elicited AMHRCs (IC50 values: 0.51 and 0.72 mg/mL) as against those of non-treated control (1.39 and 1.71 mg/mL). Overall, this study offered a feasible strategy to promote isoflavonoid production in AMHRCs with higher antioxidant activity, and also paved the way for achieving isoflavonoid overproduction via metabolic manipulations in the future.